European cinema in an era of Studio-Building: some artistic and industrial tendencies in Studiocanal's output, 2006-present. Issue 1 (2nd January 2019) - Meir, Christopher
Abstract: One of the most remarkable developments in European cinema over the last 10 years has been the creation of not one but several vertically integrated studios that produce and actively distribute films across a number of national territories. The rise of these pan-European studios signals a sea change in an industrial landscape that has long been fragmented by nation and language and film historians must begin contemplating what this change means for European cinema and global cinema more broadly. This article seeks to forward such a project by critically examining the output of Studiocanal, the foremost company involved in this trend. In so doing, it focuses on two films in particular: Tinker Tailor Soldier Spy (Tomas Alfredson, 2011) and Unknown (Jaume Collet-Serra, 2011). The article argues that these two films are emblematic of Studiocanal's two larger production strategies, one of which focuses on middlebrow production and marketing and the other which is concerned with mainstream popular genre cinema. Dividing these two tendencies, the article argues, are distinct treatments of genre, authorship and stardom, even while industrial factors relating to production and the employment of European artists unites them. Surveying these differences and similarities, the article illustrates the bigger impact that Studiocanal and by extension its fellow European studios are having on the continent's cinematic landscape while also comparing and contrasting these studios with those in Hollywood which have long dominated the global film industry.